Peningkatan kemampuan penelitian melalui pelatihan manajemen referenci dan teknik effective writing - Resekiani Mas Bakar; Andi Nasrawati Hamid (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The great academic demand to create the scientific article with high quality is the main factor that drives the partner to develop their skill in all aspects. One of the essential skills is obtaining the suitable reference with the topic in order to create the better understanding. The reference suitability between the topic and writing effectivity is the crucial element in creating academic writing, therefore, the understanding towards the function and features of journal search engine and reference management is highly important. This social partnership program aims to develop the participants’ skill to explore and find the literature, especially e-journal and practice an effective writing. This topic also relates to the use of management reference. The materials in this training consist of the application of Google Scholar and Proquest as the journal search engine and Mendeley as the reference management software. The participants in this event comes from the members of Industrial and Organizational Psychology Assosiation (APIO) South Sulawesi, APIO community, and professionals. The number of participants was 40. The result of training evaluation found that 95% of the participants gained the new knowledge and 90% considered that trainer understanding was great. Furhtermore, the involvement and enthusiasm of participants in this event suppoerted this program.